(untitled) - Sullivan, Nicholas P. (San Francisco, 2007)
You Can Hear Me Now is a powerful proof of the roles that the private sector can play in economic development. Sullivan, by picking one industry—wireless—and cleverly weaving the economics and the growth of the industry with the human dimension, provides a distinctively new perspective on what is possible. A must-read for all those who are concerned about eradicating poverty. Equally, a must-read for managers who are looking for new engines of growth
Keywords: Cell phone services industry,Information technology,Telecommunication,Ngành công nghiệp dịch vụ điện thoại di động; Developing countries,Developing countries,nước đang phát triển